(untitled) (Journal of Health, Population and Nutrition, 2010)
In the present study, a cross-sectional survey of intestinal parasitic and bacterial infections in relation to diarrhoea in Vhembe district and the antimicrobial susceptibility profiles of isolated bacterial pathogens was conducted. Stool samples were collected from 528 patients attending major public hospitals and 295 children attending two public primary schools and were analyzed by standard microbiological and parasitological techniques. Entamoeba histolytica/E. dispar (34.2%) and Cryptosporidium spp. (25.5%) were the most common parasitic causes of diarrhoea among the hospital attendees while Giardia lamblia (12.8%) was the most common cause of diarrhoea among the primary school children (p<0.05). Schistosoma mansoni (14.4%) was more common in non-diarrhoeal samples at both hospitals (16.9%) and schools (17.6%). Campylobacter spp. (24.9%), Aeromonas spp. (20.8%), and Shigella spp. (8.5%) were the most common bacterial causes of diarrhoea among the hospital attendees while Campylobacter (12.8%) and Aeromonas spp. (12.8%) were most common in diarrhoeal samples from school children. Vibrio spp. was less common (3% in the hospitals) and were all associated with diarrhoea. Antimicrobial resistance was common among the bacterial isolates but ceftriaxone (91%) and ciprofloxacin (88.6%) showed stronger activities against all the organisms. The present study has demonstrated that E. histolytica/dispar, Cryptosporidium, Giardia, and Cyclospora are common parasitic causes of diarrhoea in Vhembe district while Campylobacter spp. and Aeromonas are the most common bacterial causes of diarrhoea in Vhembe district of South Africa. Key words: Antibiotic resistance; Bacteria; Diarrhoea; Drug resistance, Microbial; Epidemiology; HIV; Parasites; South Africa DOI: 10.3329/jhpn.v27i6.4325 J Health Popul Nutr 2009 Dec; 27(6): 739-745